2011
DOI: 10.5754/hge11812
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Hepatectomy Accompanying Combined Resection of Other Organs

Abstract: Background/Aims: The present study analyzed postoperative outcomes for patients who

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Donald et al [3] demonstrated a significant reduction in SSIs following PD by simply changing the perioperative antibiotic prophylaxis from the existing colonic/abdominal surgery protocols to a regimen tailored for PD. From literature, some of the factors attributed to the development of SSIs following pancreatic surgery include malnutrition and hypoalbuminemia [10][11][12], preoperative biliary drainage [13,14] and surgery-related factors such as the development of length of surgery [15], main pancreatic duct diameter [15], pancreatic fistula, post-operative bleeding, long-term ascites and re-operation [4,15].…”
Section: Introductionmentioning
confidence: 99%
“…Donald et al [3] demonstrated a significant reduction in SSIs following PD by simply changing the perioperative antibiotic prophylaxis from the existing colonic/abdominal surgery protocols to a regimen tailored for PD. From literature, some of the factors attributed to the development of SSIs following pancreatic surgery include malnutrition and hypoalbuminemia [10][11][12], preoperative biliary drainage [13,14] and surgery-related factors such as the development of length of surgery [15], main pancreatic duct diameter [15], pancreatic fistula, post-operative bleeding, long-term ascites and re-operation [4,15].…”
Section: Introductionmentioning
confidence: 99%
“…Complete surgical resection of T4 HCCs provides the best chance of a cure 6 . HCCs with direct invasion of adjacent organs or structures require resection of not only the tumors but also the invaded organs or structures, but there are few reports documenting the safety profile and outcomes of such combined resection [7][8][9][10][11] . Most of the time, the 'invasion' is actually a dense desmoplastic reaction which cannot be differentiated on the operative field.…”
Section: Introductionmentioning
confidence: 99%
“…5 The development of SSIs is directly associated with increased length of stay, readmission rate, duration of operation, and total hospital costs. [6][7][8][9][10] The presence of organ/space infections has also been shown to lead to clinically relevant postoperative pancreatic fistula. 11 Current Centre of Disease Control (CDC) guidelines recommend administration of a first-generation cephalosporin as perioperative antibiotic prophylaxis, 12 whereas the surgical care improvement project advocate the use of second-generation cephalosporin in hepatopancreatobiliary operations.…”
mentioning
confidence: 99%
“…The most common causes of morbidity include postoperative pancreatic fistula, 4 and surgical site infections (SSI) 5 . The development of SSIs is directly associated with increased length of stay, readmission rate, duration of operation, and total hospital costs 6–10 . The presence of organ/space infections has also been shown to lead to clinically relevant postoperative pancreatic fistula 11 .…”
mentioning
confidence: 99%